Evaluatıon of fetuın-a levels ın the early stage of autoımmune thyroıdıtıs - Söbü, Elif; Yildiz Z.; Karaaslan A.; Çetin C.; Berk Akbeyaz B.; Kaya Özçora G.D.; Yilmaz B. (Acta Endocrinologica Foundation)
Context. Fetuin-A is a multifunctional protein and is known to be related to metabolic syndrome, vascular calcification, and inflammation. Objective. The purpose of this study was to determine the effects of serum fetuin-A levels on autoimmune thyroiditis without thyroid dysfunction. Subjects and Methods. This prospective casecontrol study was performed at the pediatric endocrinology outpatient clinic of a tertiary health institution in Istanbul, Turkey between July 2022 and October 2022. Serum fetuin-A levels were assessed using a human fetuin-A enzyme-linked immunosorbent assay (ELISA) kit (Elabscience Biotechnology, Houston, TX, USA). Results. The study included 86 participants, of which 42 were patients with Hashimoto’s thyroiditis (HT) and 44 were controls. Autoimmune thyroiditis without thyroid dysfunction was found to be related to lower plasma fetuin-A levels. There were no statistically significant differences in the neutrophil-to-lymphocyte ratio, fasting blood glucose level, insulin level, or HOMA-IR (Homeostatic Model Assessment for Insulin Resistance) value between the groups. A fetuin-A level of ≤162.22 μg/mL (80.95% sensitivity and 70.45% specificity) was found to support the identification of autoimmune thyroiditis. Conclusions. The findings of our study suggest that autoimmune thyroiditis without thyroid dysfunction is related to lower fetuin-A levels. Low fetuin-A levels are known to be associated with an increased risk of cardiovascular disease, suggesting that careful monitoring is required in patients with low fetuin-A levels. © 2023, Acta Endocrinologica Foundation. All rights reserved.
Keywords: cardiovascular disease; Fetuin-A; Hashimoto’s thyroiditis; HOMA-IR; neutrophil/lymphocyte ratio